Failure to Cope: The Hidden Curriculum of Emergency Department Wait Times and the Implications for Clinical Training. (January 2015) - Webster, Fiona; Rice, Kathleen; Dainty, Katie N.; Zwarenstein, Merrick; Durant, Steve; Kuper, Ayelet
Abstract : Purpose: The study explored optimal intraprofessional collaboration between physicians in the emergency department (ED) and those from general internal medicine (GIM). Prior to the study, a policy was initiated that mandated reductions in ED wait times. The researchers examined the impact of these changes on clinical practice and trainee education. Method: In 2010–2011, an ethnographic study was undertaken to observe consults between GIM and ED at an urban teaching hospital in Ontario, Canada. Additional ad hoc interviews were conducted with residents, nurses, and faculty from both departments as well as formal one-on-one interviews with 12 physicians. Data were coded and analyzed using concepts of institutional ethnography. Results: Participants perceived that efficiency was more important than education and was in fact the new definition of "good" patient care. The informal label "failure to cope" to describe high-needs patients suggested that in many instances, patients were experienced as a barrier to optimal efficiency. This resulted in tension during consults as well as reduced opportunities for education. Conclusions: The authors suggest that the emphasis on wait times resulted in more importance being placed on "getting the patient out" of the ED than on providing safe, compassionate, person-centered medical care. Resource constraints were hidden within a discourse that shifted the problem of overcrowding in the ED to patients with complex chronic conditions. The term "failure to cope" became activated when overworked physicians tried to avoid assuming care for high-needs patients, masking institutionally produced stress and possibly altering the way patients are perceived.